Association of high cost sharing and targeted therapy initiation among elderly Medicare patients with metastatic renal cell carcinoma. (1st December 2017) - Li, Pengxiang; Wong, Yu‐Ning; Jahnke, Jordan; Pettit, Amy R.; Doshi, Jalpa A.
Abstract: High out‐of‐pocket costs may limit access to oral therapies covered by patients' prescription drug benefits. We explored financial barriers to treatment initiation in patients newly diagnosed with metastatic renal cell carcinoma (mRCC) by comparing Medicare Part D patients with low out‐of‐pocket costs due to receipt of full low‐income subsidies (LIS beneficiaries) to their counterparts who were responsible for more than 25% cost sharing during Medicare's initial coverage phase (non‐LIS beneficiaries). We used 2011–2013 100% Medicare claims for non‐LIS and LIS beneficiaries newly diagnosed with metastases in the liver, lung, or bone to examine targeted therapy treatment initiation rates and time to initiation for (1) oral medications (sorafenib, sunitinib, everolimus, pazopanib, or axitinib) covered under Medicare's prescription drug benefit (Part D); (2) injected or infused medications (temsirolimus or bevacizumab) covered by Medicare's medical benefit (Part B); and (3) any (Part D or Part B) targeted therapy. The final sample included 1721 patients. On average, non‐LIS patients were responsible for out‐of‐pocket costs of ≥2, 800 for their initial oral prescription, as compared to ≤6.60 for LIS patients. Compared to LIS patients, a lower percentage of non‐LIS patients initiated oral therapies (risk‐adjusted rates, 20.7% vs. 33.9%; odds ratio [OR] = 0.49, 95% CI: 0.36–0.67, P < 0.001) and any targeted therapies (26.7% vs. 40.4%, OR = 0.52, 95% CI: 0.38–0.71, P < 0.001). Non‐LIS patients were also slower to access therapy. High cost sharing was associated with reduced and/or delayed access to targeted therapies under Medicare Part D, suggesting that financial barriers play a role in treatment decisions. Abstract : Medicare Part D beneficiaries newly diagnosed with metastatic renal cell carcinoma have significantly lower rates of oral and any targeted therapy initiation—and are slower to initiate treatment—when they are responsible for high out‐of‐pocket costs. Financial barriers may be factoring into treatment decisions; this warrants further investigation.